2020
DOI: 10.1177/0306624x20919710
|View full text |Cite
|
Sign up to set email alerts
|

Internal and External Barriers to Help Seeking: Voices of Men Who Experienced Abuse in the Intimate Relationships

Abstract: This qualitative study explores internal and external barriers to help seeking among 41 men from four English-speaking countries who self-reported victimization from a female intimate partner. Twelve online focus groups were conducted and themes were identified inductively at a semantic level. Six identified themes represented four internal (blind to the abuse, maintaining relationships, male roles, and excuses) and two external barriers to help seeking (fear of seeking help and nowhere to go). Most participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
93
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 41 publications
13
93
1
Order By: Relevance
“… Note. The same table appears in other articles published with these data (Dixon et al, in press; Lysova et al, in press). …”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“… Note. The same table appears in other articles published with these data (Dixon et al, in press; Lysova et al, in press). …”
Section: Methodsmentioning
confidence: 69%
“…For this study, we analyzed responses to Question 4 to provide an in-depth focus on men’s help-seeking that involved a CJS response. The other questions are the focus of other publications (Dixon et al, in press; Douglas et al, 2018; Lysova et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…We are aware because of the length of this process there is new evidence which could be assimilated into this IMMS. Three multi-country studies by the same research team have been published in 2020 [37][38][39].. One of these new studies reenforces the findings of our IMMS on help seeking by male victims and service provision [37]. The second study specifically examines male victims experiences of the criminal justice system and this would add new material to our IMMS [38].…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…In some cases, the police showed no empathy or any willingness to listen to the experiences of male victims of IPA (Lysova et al, 2020a(Lysova et al, , 2020bMcCarrick et al, 2016). In a study of 372 male victims of IPA in the Netherlands, less than 32% of the men had approached the police about their victimization, while only 15% of the men registered an official report to the police (Drijber et al, 2013).…”
Section: Male Victims and Police Responsementioning
confidence: 99%
“…Domestic Abuse Helpline for Men found that 72% of the men claimed that their abusers manipulated the court system to gain sole custody of the children or obtained an unwarranted restraining order against the victim (Hines et al, 2007). Qualitative studies of male victims of IPA found that men were not given a fair hearing in the court despite the evidence of female-perpetrated abuse, that they lost custody of their children more often, and that they faced a much higher burden of proof than female victims (Cook, 2009;Lysova et al, 2020aLysova et al, , 2020b.…”
Section: Male Victims and The Courtsmentioning
confidence: 99%